Dose-dependent decrease of platelet activation and tissue factor by omega-3 polyunsaturated fatty acids in patients with advanced chronic heart failure - Moertl, Deddo; Berger, Rudolf; Hammer, Alexandra; Hutuleac, Raisa; Koppensteiner, Renate; Kopp, Christoph W.; Steiner, Sabine (Thrombosis and Haemostasis, 2011)
Chronic heart failure (CHF) is characterised by activation of neuroendocrine and inflammatory pathways, and both are linked to a prothrombotic state. Treatment with omega-3 polyunsaturated fatty acids (n3-PUFA) showed significant benefits including mortality reduction in CHF, but exact mechanisms of action are still unclear. We investigated the effects of n3-PUFA on markers of platelet activation and thrombogenesis in patients with severe CHF. Thirty-six patients with non-ischaemic CHF (LVEF<35%, NYHA class>2) under optimised therapy were randomised to supplementation with 1g/day or 4g/day n3-PUFA, or placebo for 12 weeks. Using whole-blood flow cytometry, monocyteplatelet aggregates characterised by CD14+/CD42b+ co-expression and monocytic tissue factor (TF) were determined. Plasma levels of P-selectin, sCD40L, fibrinogen, prothrombin fragment F1.2, TF and proinflammatory markers (high sensitive[hs] interleukin-6, hsCRP, hsTNFalpha, monocyte chemotactic protein-1) were measured by immunoassay. Supplementation with 1g/day and 4g/day n3-PUFA but not placebo significantly reduced monocyte-platelet aggregates in a dose-dependent manner (p for trend=0.02 across the groups). A dose of 4g/day but not 1g/day n3-PUFA significantly decreased P-selectin (p=0.03). Plasma TF decreased dose-dependently upon n3-PUFA supplementation (p for trend=0.02), paralleled by a significant decrease of TF+-monocytes (p for trend=0.01). The amount of 4g/day n3-PUFA exhibited modest anti-inflammatory effects with a significant reduction of hs interleukin-6 (p<0.01) and a trend-wise reduction of hsTNF-alpha (p=0.09). No changes were seen for sCD40L, fibrinogen, hsCRP and monocyte chemotactic protein-1, while F1.2 was decreased by 4g/day n3-PUFA (P=0.03). In patients with severe non-ischaemic CHF, treatment with n3-PUFA leads to a dose-dependent decrease of platelet activation and TF. Higher dosage exhibits also anti-inflammatory effects.* ClinicalTrials.gov registration number: NCT00149409
Keywords: Fatty acids; heart failure; inflammation; platelets; tissue factor